Analysis of dose–TSH response effect of levothyroxine soft-gel formulation - Trimboli, Pierpaolo; Piticchio, Tommaso; Dadda, Zeno; Stramazzo, Ilaria; Gamarra, Elena; Ruinelli, Lorenzo; Virili, Camilla (Frontiers in Endocrinology, 2024)
Background Hypothyroidism is treated with daily levothyroxine (LT4). In recent years, soft gel caps of LT4 (LT4-C) have been commercialized, and their performance has been optimized. Since guidelines recommend dose LT4 according to the tablet preparation efficacy, the present study was undertaken to obtain data about the daily requirement, normalized per body weight, of LT4-C. Methods Patients undergoing LT4-C after total thyroidectomy and radioiodine treatment for differentiated thyroid carcinoma were selected. There was no specific indication of suppression of TSH (i.e., <0.5 or <0.1 mIU/L). Patients were required to maintain a stable LT4 dose during the study period. Patients with interfering factors were excluded from this study. Results Thirty patients were enrolled (18 females and 12 males; median age, 50 years; median body weight, 71 kg; median LT4-C dose, 1.71 µg/kg/day). The analysis of patient age did not reveal any differences. The LT4-C dose correlated with free-T4 p = 0.03), but not with TSH (p = 0.42) and free-T3 (p = 0.13). TSH was <1.0 mIU/L in 90% of the cases. The LT4-C dose–TSH response effect was analysed by probit regression model: the probability to achieve TSH <1.0 mIU/l was 99% with a dose of 1.84 (95%CI 1.57–2.12) µg/kg/day, 75% with a dose of 1.38 µg/kg/day (95%CI 1.17–1.59), and 50% with a dose of 1.20 (95%CI 0.96–1.43). At ROC curve analysis, the most accurate cut-off of LT4-C dose to achieve TSH <1.0 mIU/l was 1.53 ug/kg/day with 70% sensitivity and 100% specificity. Conclusions Athyreotic patients can be initially treated with an LT4-C dose lower than previously stated. Therefore, further prospective studies are warranted.